Approach Generalized Structured Component Analysis (GSCA) Method for Structural Equation Modeling Unidimensional - Susanti, Nawal Ika; Tirta, I Made; Dewi, Yuliani Setia (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
There are two types of Structural Equation Modeling is covarience or CB-SEM and variance or Partial Least Square SEM. The two types have advantages and disadvantages of each so Hwang & Takane propose a new method, namely the Generalized Structured Component Analysis (GSCA) which is a method that has been developed to complement the existing deficiencies in the Partial Least Square. Researchers using the GSCA for structural model factors affecting the nutritional status of children under five who are unidimensional structural equation. GSCA method in estimating the parameters using the method of Alternating Least Squares (ALS) and to estimate the standard error of the parameter estimates using the bootstrap method. The results of this study are all variables that indicator is a measure of valid and reliable to measure latent variables and also research model is a model that can be acceptable and in accordance with the existing conditions in the field.